Aplikasi Mobile untuk Kendali Simulasi Smart Home Berbasis Lokasi - Alvin Tanujaya Sutanto; Henry Novianus Palit; Resmana Lim (Jurnal Infra, 2019)
Nowadays, there are many smart home that already developed and sold. Because of smart home with all of the facilities gave a comfortable feeling for householders. In this thesis an aplication is made to make use of GPS as positioning for hardware and user. Besides GPS, arduino also useful for controling hardware. This application will run on Android device. Application will show user’s and hardware’s position all the time. Application can also make alarm for AC to turn on or off and application also can make radius that will help as geofence.